2015
DOI: 10.1080/0361073x.2016.1108712
|View full text |Cite
|
Sign up to set email alerts
|

Task-Related Vigilance During Word Recognition in Noise for Older Adults with Hearing Loss

Abstract: Background/Study Context Vigilance refers to the ability to sustain and adapt attentional focus in response to changing task demands. For older adults with hearing loss, vigilant listening may be particularly effortful and variable across individuals. This study examined the extent to which neural responses to sudden, unexpected changes in task structure (e.g., from rest to speech recognition epochs) were related to pupillometry measures of listening effort. Methods Individual differences in the task-evoked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 66 publications
0
31
1
Order By: Relevance
“…This finding is consistent with prior research demonstrating increased gray matter density in the auditory cortices of musicians, 42,43 as well as higher activation in the STG. 43 Although increasing listening effort has been associated with increased activity in the STG, 44 the observed enhanced activity in the auditory cortices is unlikely to reflect listening effort. Prior research has shown that differences in brain activation between musicians and nonmusicians are also observed when both groups matched behavioral performance in auditory WM.…”
Section: Effects Of Musical Trainingmentioning
confidence: 99%
“…This finding is consistent with prior research demonstrating increased gray matter density in the auditory cortices of musicians, 42,43 as well as higher activation in the STG. 43 Although increasing listening effort has been associated with increased activity in the STG, 44 the observed enhanced activity in the auditory cortices is unlikely to reflect listening effort. Prior research has shown that differences in brain activation between musicians and nonmusicians are also observed when both groups matched behavioral performance in auditory WM.…”
Section: Effects Of Musical Trainingmentioning
confidence: 99%
“…In addition, speech comprehension is more effortful with increased linguistic complexity—operationalized as the use of semantically ambiguous words or syntactically complex sentences (Bilenko, Grindrod, Myers, & Blumstein, ). These manipulations in perceptual and cognitive difficulty are reflected in behavioral performance (e.g., lower accuracy in speech identification or comprehension, increased response time), and physiological measures in pupil dilation (Koelewijn, Zekveld, Festen, & Kramer, ; Kuchinsky et al, ; Zekveld, Kramer, & Festen, ). Increased pupil diameter and decreased behavioral performance are considered manifestations of mental effort (Kahneman, ; McGarrigle et al, ; Westbrook & Braver, ), and these indices accompany effortful listening when speech stimuli are manipulated using either of the three manipulations described above.…”
Section: Introductionmentioning
confidence: 99%
“…Listeners' subjective feeling is affected both by external task demands 663 (SNR levels and TASK), and one's evaluation of recall success. Note that all three 664 measures (pupillary response, word recall performance and subjective rating) also 665 significantly correlated with age, making it possible that the correlations observed were 666 variable, for instance individual cognitive capacity[23,27,44,53,78,79]. 667To summarise, while behavioural performance (i.e., recall) and subjective rating 668 indicate the final outcome of a series of cognitive processes, pupillometry can reveal the 669 difference in listening effort between conditions, the temporal dynamics of different 670 stages of cognitive processing, as well as the allocation policy of cognitive resources.However, only a handful of studies have looked into the dynamics of pupillary response 672 in realistic conditions, where listening is not the only task demanding cognitive673 resources.…”
mentioning
confidence: 99%